1996
DOI: 10.1007/bf00823588
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the hemodynamic effects of metoprolol and carvedilol in hypertensive patients

Abstract: Metoprolol and carvedilol are widely used in the treatment of hypertension, but no randomized comparison of their hemodynamic activity has been previously reported. Their comparative effects on heart rate, systemic blood pressure, and echocardiographically determined aortic and femoral artery blood flow were measured at rest and at 2 and 24 hours after the first dose of each drug, and again after 4 weeks of sustained monotherapy in 12 male and 12 female patients, aged 36-68 years with uncomplicated sustained h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 12 publications
0
4
0
2
Order By: Relevance
“…In a doubleblind comparison with propranolol in patients with essential hypertension, carvedilol did not reduce forearm blood flow, in contrast to propranolol (50). In a short-term randomized hemodynamic comparison between carvedilol and metoprolol it was confirmed that CO did not change with carvedilol even after 4 weeks of treatment whereas a significant reduction was seen in the metoprolol-treated patients (51).…”
Section: Hemodynamics In Hypertensionmentioning
confidence: 87%
“…In a doubleblind comparison with propranolol in patients with essential hypertension, carvedilol did not reduce forearm blood flow, in contrast to propranolol (50). In a short-term randomized hemodynamic comparison between carvedilol and metoprolol it was confirmed that CO did not change with carvedilol even after 4 weeks of treatment whereas a significant reduction was seen in the metoprolol-treated patients (51).…”
Section: Hemodynamics In Hypertensionmentioning
confidence: 87%
“…Beta‐blockers lead to peripheral vasoconstriction that results in erectile dysfunction, decreased renal blood flow and increased peripheral resistance that limits the antihypertensive effect of beta‐blockers. However, peripheral vasoconstriction also decreases the microvascular surface area within the skeletal muscle that results in a decreased surface area for insulin‐mediated entry of glucose into muscle and increased insulin resistance [46,47].…”
Section: Disadvantages Of Beta‐blockers In the Diabetic Patientmentioning
confidence: 99%
“…В отличие от β 1 -селективных блокаторов карведилол блокирует также β 2 -и α-адренорецепторы. Блокада α-адренорецепторов приводит к периферической вазодилатации и тем самым к уменьшению периферического сопротивления, что играет роль в снижении артериального давления (АД) [4,5]. Типичное для БАБ неблагоприятное влияние на обмен глюкозы и липидов также уменьшается за счет дополнительного αадреноблокирующего эффекта [6,7].…”
Section: клиническая и фармакокинетическая эквивалентность оригинальнunclassified